Antioxidant system by the consentration levels of the free and connected albuminous sulphidic and disulphidic groups in a tear liquid depending on degree of myopia in children (Ukrainian Journal of Ophthalmology, 2026)
Material and methods. There were 34(68 eyes) children at the age of 8–14 under observation. Among them there were children with myopia of mild degree (7), moderate degree (10), and high degree (7) as well as a control group healthy of children of the same age — 10 people. Visometry, ophthalmometry, refractometry in conditions of cycloplegia biomicroscopy and ophthalmocopy were made in all patients. Free and connected SH and S-S — groups in the tear fluid were determined by spectrocolormeter Spekol-210 with a wave length of 356 nm and 412 nm accordingly. Results. It was established that in average values of connected SH and S-S — groups’ levels in the tear fluid had no significant difference in comparison with values in healthy children but it was found that SS — free and connected groups had the tendency to increase in average by (4.8–14.5) % depending on the myopic degree. Free SH- groups content in tear of children with high myopia was lower in comparison with the control group by 28 % (54. 2 ± 5.5) units, p
Keywords: Myopia in children; antioxidant system